2008
DOI: 10.1097/01.prs.0000299384.53131.87
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Centrifugation on Cells and Tissues in Liposuction Aspirates: Optimized Centrifugation for Lipotransfer and Cell Isolation

Abstract: Excessive centrifugation can destroy adipocytes and adipose-derived stem cells, but appropriate centrifugation concentrates them, resulting in enhanced graft take. The authors tentatively recommend 1200 g as an optimized centrifugal force for obtaining good short- and long-term results in adipose transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(149 citation statements)
references
References 24 publications
2
141
0
2
Order By: Relevance
“…However, like aspiration pressure, the physical effects of centrifugation may have an effect on SVF viability and the number of ASCs available for culture. A study by Kurita and colleagues 31 has shown that speeds in excess of 3,000 x g can damage the ASC. However, speeds should be significant enough to ensure adequate pelleting of the SVF.…”
Section: Discussionmentioning
confidence: 99%
“…However, like aspiration pressure, the physical effects of centrifugation may have an effect on SVF viability and the number of ASCs available for culture. A study by Kurita and colleagues 31 has shown that speeds in excess of 3,000 x g can damage the ASC. However, speeds should be significant enough to ensure adequate pelleting of the SVF.…”
Section: Discussionmentioning
confidence: 99%
“…43 The recovery of ASCs can be improved further by manipulating the centrifugation speed. 45 Investigators have achieved optimal cell recovery using a centrifugation speed of 1200g based on the subsequent formation of a human-derived adipose tissue depot following implantation in an immunodeficient murine model. 45 The cell isolation process requires the manipulation of large volumes of lipid-laden cells, presenting potential risks to equipment and personnel.…”
Section: Cell Isolation and Mechanical Devicesmentioning
confidence: 99%
“…45 Investigators have achieved optimal cell recovery using a centrifugation speed of 1200g based on the subsequent formation of a human-derived adipose tissue depot following implantation in an immunodeficient murine model. 45 The cell isolation process requires the manipulation of large volumes of lipid-laden cells, presenting potential risks to equipment and personnel. To facilitate the process, several groups have fabricated devices to automate the cell isolation.…”
Section: Cell Isolation and Mechanical Devicesmentioning
confidence: 99%
“…The cells may be damaged due high G-forces (Kurita et al, 2008)  It is a time and labor-consuming process  High fat concentrations may cause clumping and more difficult flow during re-injection One of the most confusing metrics in fat grafting is a lack of standardization when one discusses "percent yields". Once fat is lipo-aspirated as donor graft there are an infinite number of different concentrations of adipocyte volume relative to non-adipocyte volume (blood, serum, crystalloid) that can be reached prior to grafting the recipient site.…”
mentioning
confidence: 99%